Cooperatives as Pillar of Economy to Improve Agriculture Production and Marketing - Bhattarai, Rudra; Pandit, Manashi (Nepal Public Policy Review, 2023)
This paper focuses on the important role played by cooperatives in agriculture production and marketing in Nepal. The paper evaluates the role of cooperatives, their contribution to agriculture, current policies that have paved the way for development within the agriculture and cooperative sectors and recommendations for improving agriculture production and marketing. The methodology employed includes a review of existing literature on agriculture and cooperative policies, as well as discussions with key informants in the cooperative movement. The study highlights the need for support from government and non-government agencies to improve the service of agricultural cooperatives in various ways, particularly through policy intervention. The paper provides policy recommendations for the future, including the need for improved coordination between government agencies and cooperatives, capacity-building programs, commercialization of agro-products, ways of increasing agro-productivity and capacity-building for cooperative leaders, and better access to credit and markets. Overall, the study underscores the importance of cooperatives in the sustainable development of the agriculture sector in Nepal.